Software Bantu Pembuka Aplikasi Pada Dekstop Berbasis Voice Recognition - Akuwan Saleh; Rido Akbar I; Hari Wahjuningrat S (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2021)
The human desire to make it easier to use a tool in order to increase the effectiveness of work production becomes a guide in the world of work. However, physical limitations or physical disabilities, especially the hands, make it difficult for someone to work using these tools. Therefore an assistive software was made to solve these problems, by utilizing the recognition of natural human characteristics using voice or voice recognition. Assistive software opening applications on a computer desktop with voice commands which are then converted into text using processing software with the help of the webscocket and speech-to-text library from Google and the results are processed to open the desired application by the user. In this paper, an application that has been made is able to convert voice to text and can open applications on the desktop so that it makes it easier for users to operate applications on a computer with a system success rate for speech recognition reaching 91.5%.